2010
DOI: 10.1183/09031936.00204209
|View full text |Cite
|
Sign up to set email alerts
|

14 nights of intermittent hypoxia elevate daytime blood pressure and sympathetic activity in healthy humans

Abstract: Obstructive sleep apnoea syndrome (OSAS) causes nocturnal chronic intermittent hypoxia (IH) that contributes to excess cardiovascular morbidity. To explore the consequences of IH, we used our recently developed model of nocturnal IH in healthy humans to characterise the profile of this blood pressure increase, to determine if it is sustained and to explore potential physiological mechanisms.We performed 24-h ambulatory monitoring of blood pressure in 12 healthy subjects before and after 2 weeks of IH exposure.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
175
3
21

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 254 publications
(206 citation statements)
references
References 47 publications
7
175
3
21
Order By: Relevance
“…Our data are consistent with the literature, which reports the following: (1) an independent association between OSA and hypertension in humans34 and (2) a determinant role of chronic IH in inducing elevation of arterial and blood pressure in healthy humans and animals exposed to IH 35, 36, 37. We further demonstrated that, in addition to the elevation of arterial blood pressure, IH also induces an arterial inflammatory remodeling with subsequent stiffening.…”
Section: Discussionsupporting
confidence: 92%
“…Our data are consistent with the literature, which reports the following: (1) an independent association between OSA and hypertension in humans34 and (2) a determinant role of chronic IH in inducing elevation of arterial and blood pressure in healthy humans and animals exposed to IH 35, 36, 37. We further demonstrated that, in addition to the elevation of arterial blood pressure, IH also induces an arterial inflammatory remodeling with subsequent stiffening.…”
Section: Discussionsupporting
confidence: 92%
“…1,2 The repetitive occurrence of apneas and hypopneas with the associated intermittent hypoxia sequence causes acute surges in blood pressure (BP), sleep fragmentation, and chronic sympathetic activation that ul-timately lead to sustained hypertension. 3 A large body of evidence from animal models, intermittent hypoxia exposure of healthy humans 4 and epidemiological studies support an independent role of OSA in the pathogenesis of daytime hypertension. 2,5,6 However, it has been shown that CPAP, the first line therapy for OSA, has a limited effect on blood pressure control, 7,8 and the size of the effect is highly related to the duration of nightly CPAP usage.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study in healthy humans, IH significantly increased sympathetic activity and daytime blood pressure after a single night of exposure. The baroreflex control of sympathetic outflow declined (Tamisier et al, 2011). Surges in sympathetic nervous system activity associated with apneic events have also been related to antifibrinolytic activity reflected by elevations in PAI-1 (von & Dimsdale, 2003).…”
Section: Enhanced Sympathetic Trafficmentioning
confidence: 99%